2020
DOI: 10.3390/app10113872
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Smart Parking Systems

Abstract: The large number of vehicles constantly seeking access to congested areas in cities means that finding a public parking place is often difficult and causes problems for drivers and citizens alike. In this context, strategies that guide vehicles from one point to another, looking for the most optimal path, are needed. Most contributions in the literature are routing strategies that take into account different criteria to select the optimal route required to find a parking space. This paper aims to identify the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(20 citation statements)
references
References 287 publications
0
18
0
2
Order By: Relevance
“…In this section, we outline the research method used. To justify this research method and the scope of our work, we first highlight and discuss nine surveys and reviews that cite the datasets analyzed in this work (Meduri & Estebanez, 2018;Mahmud et al, 2020;Paidi et al, 2018;Enríquez et al, 2017;Kawade et al, 2020;Barriga et al, 2019;Chen et al, 2019;Zantalis et al, 2019;Diaz Ogás et al, 2020). In Meduri & Estebanez (2018), a brief review of Deep Learning (DL) based approaches for parking lots is given.…”
Section: Motivationmentioning
confidence: 99%
“…In this section, we outline the research method used. To justify this research method and the scope of our work, we first highlight and discuss nine surveys and reviews that cite the datasets analyzed in this work (Meduri & Estebanez, 2018;Mahmud et al, 2020;Paidi et al, 2018;Enríquez et al, 2017;Kawade et al, 2020;Barriga et al, 2019;Chen et al, 2019;Zantalis et al, 2019;Diaz Ogás et al, 2020). In Meduri & Estebanez (2018), a brief review of Deep Learning (DL) based approaches for parking lots is given.…”
Section: Motivationmentioning
confidence: 99%
“…Difficulties in finding a suitable parking place encountered globally result in traffic congestion and air pollution issues that need to be addressed, and urgently. Readers are highly encouraged to look into the survey conducted by Diaz et al [ 18 ], which extensively investigated the smart parking systems and classified them into six categories: parking reservation systems, parking guidance and information systems, crowdsourcing in intelligent transportation systems, centralized assisted parking search, agent-based guiding systems, and electrical vehicle parking systems. Several other research studies have been conducted to address the car parking issues, and some of the latest solution approaches are highlighted in this section.…”
Section: Cooperative Driving—a Comprehensive Analysis Of the Research Literaturementioning
confidence: 99%
“…To sum up, the exhaustive survey conducted on smart parking systems (SPS) by Reference [ 18 ] uncovered several open issues and challenges in the SPS, such as: the consideration of user preferences while suggesting the optimally available parking spaces to the drivers; highlighting that the implementation of SPS should be context-sensitive since all cities have different infrastructures, budgets, and societies; and found that less work has been done on rescheduling the routes established by the SPS taking towards the parking slot in case of unexpected event triggers. …”
Section: Cooperative Driving—a Comprehensive Analysis Of the Research Literaturementioning
confidence: 99%
“…Several review articles have been presented in the literature that explore, classify, and discuss the technical aspects of smart parking solutions [16][17][18][19]. This section discusses related smart parking systems from existing studies, obtained by searching using the keywords 'smart parking' and 'IoT parking' in several databases such as ISI Web of Science and Scopus.…”
Section: Related Workmentioning
confidence: 99%